Do prisons cause radicalization? Order, leadership, political charge and violence in two maximum security prisons - Williams, Ryan (The British journal of criminology, 2023)
Sociological studies of prisons require expanded methodologies and interdisciplinary concepts to address challenges posed by changing prisoner demographics and transformed geopolitics. We aim to revitalize sociological inquiry on prisons and prisoner leadership by focussing on the question of whether prisons cause radicalization. Our findings support those of the most persuasive original studies: distinct prison climates generate different hierarchies, only some of which are violent. Through extensive fieldwork we explore the differences between a prison with high levels of ‘political charge’, or anger, and another with less, drawing on extremist events that unfolded over time. We contrast the dangerous dynamics of prison 1 with the more fluid, prosocial religious explorations facilitated by prison 2, considering the implications for prison radicalization studies.